Assessing Atmospheric Instability over the Bay of Bengal during October and November Months between 2007 – 2018 (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
An attempt has been made in this research to delineate a pattern for atmospheric instability during the months of October and November from 2007 to 2018. The results show an alarming trend of increasing instability throughout the study period. The average temperature at 2-meters height around the Bay of Bengal has changed significantly over time. Most notably, the gap between monthly average highest and monthly average lowest temperatures (at 2-meters height) is more or less increasing from 2007 to 2018 – ranging from 3.0 degrees to 11.0 degrees Celsius. Similar tendencies are observed for CAPE (Convective Available Potential Energy) as well – with the highest value of more than 3000 J/Kg. The findings of this research will help in understanding the prevailing conditions over the Bay, and also enable better preparedness for any potential severe convective activities.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(2), 2020, P 45-54